(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
Feeds and fertilizer production from tanned skin-cut wastes is the most direct phenomenon of chromium eco-toxicity leading to food chain contamination in Bangladesh. Tanning industries of Hazaribagh at Dhaka process some 220 t of hide per day with release of 600-1000 Kg tanned skin-cut waste (SCW) per ton processed hide. The SCW is protein-rich and unscientifically used to produce poultry and fish feeds, and organic fertilizer. A huge migration of chromium can happen into poultry products, fish and vegetables, and further bio-magnify into food chain. The target population is also huge. It is reported that feed ingredients produced from SCW contained chromium at levels as high as 2.49%. As Cr(VI) is the most toxic species of chromium, reduction of Cr(VI) to Cr(III) prior to be used as feed ingredients and fertilizers can ensure safer input of chromium in toxicological point of view. Samples have been collected to isolate microorganisms from effluent sites of Hazaribagh tanning area using Lauria-Bertani medium with added Cr(VI) as K2Cr2O7. The successful as well as apparently differing colonies (isolates IF-10 to IF-12, IF-16, and IF-19 to IF-23) have been studied for growth characterization under differing Cr(VI) concentrations up to 1500 mg/L. Cultural and biochemical tests of the isolates have narrowed the range into 3 strains. These strains have been identified by 16s rRNA gene sequence analysis. The isolates are found to be Escherichia sp. (Isolate IF-10 to IF-12, Strain IFR-I), Staphylococcus aureus (Isolate IF-16, Strain IFR-II), and Pediococcus pentosaceus (Isolate IF-19 to IF-23, Strain IFRIII). The organisms have been studied for Cr (VI) reduction-ability in growth dependent manner which are found successful up to 82.88 % for Staphylococcus aureus, and 100 % for Escherichia sp. and Pediococcus pentosaceus within 24 h. Key words: Bacteriology, Enzymatic reduction, Bioremediation, Chromium eco-toxicity Â doi: 10.3329/bjsir.v43i4.2236 Bangladesh J. Sci. Ind. Res. 43(4), 455-466, 2008